Partnering local communities for sustainable urban agriculture: the LA 21 Kuala Lumpur initiatives - Mohd Saud, Halimi; Mohd Satar, Mohd Ghazali (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
In May 2014, Faculty of Agriculture, Universiti Putra Malaysia signed a Memorandum of Understanding as one of the strategic partners under Local Agenda 21 Kuala Lumpur. Under this MOU, the faculty is one of the tripartite agencies comprising of local communities, government agencies and NGOs working together under the United Nations Conference on Environment and Development Local Agenda 21 (LA 21). LA21 is a global action blueprint for sustainable development at local level, which was adopted at the Earth Summit in Rio de Janeiro in 1992. Under this initiative, LA21 KL has one of the themes “Bandaraya Bersih & Indah” or “Clean & Beautiful City” and the faculty works together with Kuala Lumpur City Hall to engage communities to adopt urban agriculture in their local environment. As a partner who provides technical expertise in urban agriculture, the faculty works with local communities towards a sustainable urban agriculture projects. To date, about twenty communities, schools and NGOs are involved at various stages of developing their urban agriculture projects. Each community, school or NGO project will have an academic and technical staff from the faculty who acts as advisors. The staff will ensure that the projects are properly planned and the correct methods are used to achieve their objective of having a sustainable urban agriculture in their localities. The initial part of the initiatives is to identify a suitable location for their urban agriculture activities under the purview of Kuala Lumpur City Hall, followed by cleaning and preparation of the ground for urban farming whether using conventional or soilless culture methods. In addition, to encourage the interest of the community, a basic agriculture and farming course and workshop was also conducted for the communities. To ensure that it is correctly implemented, the staff of the faculty monitor and evaluate the progress and this is reported to Kuala Lumpur City Hall. LA21 KL Herbal Garden is one of the several success story which is highlighted.